Determining The Presence of Photocatalytic Titanium White Pigments via Embedded Paint Sample Staining: A Proof of Principle. (4th July 2019) - van Driel, Birgit Anne; van der Meer, Sharon R.; van den Berg, Klaas Jan; Dik, Joris
ABSTRACT: Twentieth century paints often contain titanium dioxide and zinc oxide based white pigments that can range from photostable to highly photocatalytic. Photocatalytic pigments can cause the degradation of paint upon UV exposure, whereas photostable pigments may be benign or can protect paintings from degradation. Hence, knowing whether or not a pigment is photocatalytic is of high importance for risk assessment and the subsequent decision making process concerning storage and exposure conditions of objects. Here we present a proof of principle, focused on titanium white paints, for an easy-to-use and low-tech application of a commercial photocatalytic activity indicator ink (PAII) on embedded paint samples or cross sections. This test determines, qualitatively, if a photocatalytic pigment is present in a white paint sample. The PAII paint sample staining application shows an obvious color change, within five minutes of UV irradiation, for paint samples containing photocatalytic pigments. A microscope with a camera and a UV source are the only necessary equipment for the application of this method. A quantitative image processing protocol is also proposed as an extension of the staining method by applying open source software analysis to measure the color change using photographs. The test was evaluated on reference paints with well-characterized pigments and applied on samples from modern paintings by Piet Mondriaan, Robert Ryman, and Lucebert, indicating the presence of harmful photocatalytic pigments in these cases. The novel application of a commercial ink on paint samples offers a simple test, not just for assessment of photocatalytic activity of titanium white pigments, but which may in future be applied for the detection of photoactive forms of zinc white and other potentially harmful semiconductor pigments in art objects.